2017
DOI: 10.1017/s0007114517003002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal conjugated linoleic acid modulates TAG metabolism in adult rat offspring

Abstract: Conjugated linoleic acid (CLA) might regulate the lipid depots in liver and adipose tissue. As there is an association between maternal nutrition, fat depots and risk of offspring chronic disease, the aim was to investigate the effect of maternal CLA consumption on TAG regulation and some inflammatory parameters in adult male rat offspring receiving or not receiving CLA. Female Wistar rats were fed control (C) or CLA-supplemented (1 %, w/w) diets during 4 weeks before and throughout pregnancy and lactation. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
6
11
0
Order By: Relevance
“…In the present study, using an equimolecular mixture of c9, t11-CLA and t10,c12-CLA isomers, we found, as expected, that CLA was incorporated in the serum, liver and EWAT of the HFþCLA/HFþCLA group but was not detected in the HFþCLA/ HF group, as previously observed (22) . In agreement with previous results from our laboratory (42) and from other authors (43,44) , the incorporation of c9,t11-CLA was higher than that of the t10, c12-CLA isomer in EWAT > liver > serum.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, using an equimolecular mixture of c9, t11-CLA and t10,c12-CLA isomers, we found, as expected, that CLA was incorporated in the serum, liver and EWAT of the HFþCLA/HFþCLA group but was not detected in the HFþCLA/ HF group, as previously observed (22) . In agreement with previous results from our laboratory (42) and from other authors (43,44) , the incorporation of c9,t11-CLA was higher than that of the t10, c12-CLA isomer in EWAT > liver > serum.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, taking into account that the same results were observed in both offspring groups, consuming or not consuming CLA after weaning, and that we did not detect CLA in the liver of the HFþCLA/HF group, we could hypothesise that an early-life CLA programming mechanism that controls liver steatosis may be involved. Similar mechanisms of TAG regulation were previously observed in a study that investigated the influence of maternal CLA on TAG metabolism in adult offspring rats fed a normo-energetic diet (22) .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Among all CLA isomers, t10,c12-CLA was found to be responsible for fat-reducing effects ( House et al., 2005 ). Previous studies showed that maternal supplementation with a 0.5% CLA mixture increased t10,c12-CLA incorporation in the serum, liver, and adipose tissue of offspring and decreased triglyceride ( TG ) accumulation and adipose tissue deposition ( Reynolds et al., 2015 ; Lavandera et al., 2017 ; González et al., 2020 ; Fu et al., 2021 ). However, CLA treatment also decreased the synthesis of monounsaturated fatty acids ( MUFA s) from saturated fatty acids ( SFA s) by inhibiting Δ-9 desaturase activity in hen livers and increasing the ratio of SFAs:MUFAs in yolk sacs ( Muma et al., 2006 ; Fu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%